SIGNIFICANCE AND CHALLENGES ON ADAPTATION OF DIGITAL AND DISTANCE LEARNING AMONG PHYSICAL EDUCATION STUDENTS (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study examines the significance and challenges among the physical education students towards digital and distance learning. An online survey technique was adopted to conduct this study in Aligarh district schools with a number of 464 participants. The age group ranged from 15 to 19 years for all participants. All the students who participated in this survey were currently attending online classes during the COVID-19 outbreak. Semi-structured online questionnaires developed with Google Forms. A self-developed questionnaire was used to collect data. Questions are based on a five-point Likert scale from Strongly Agree to Strongly Disagree. The survey was circulated on the social media platform among students. Students give their consent and provide appropriate answer to each question. The average time taken by a student was 4-5 minutes to complete the survey. The results demonstrate that the physical education students are not voluntarily accepting online classes during the lockdown period, student are attending online classes the first time in their lives, many students have not been able to afford online classes, students have experienced stress due to the COVID-19 pandemic, and they feel so online learning is an added burden on them, the institution does not provide any technical training for student to become familiar with the online classes, and the students were not completely satisfied with the quality of these online learning classes. There is a need for teacher and school management to take measures to avoid student inconveniences in organizing digital and distance teaching and learning seamlessly.